The archaeology of island colonization : global approaches to initial human settlement - Napolitano, Matthew F.; Stone, Jessica H.; DiNapoli, Robert J.; Thompson, Victor D. (Society and ecology in island and coastal archaeology., 2021)
"This volume details how new theories and methods have recently advanced the archaeological study of initial human colonization of islands around the world, including in the southwest Pacific, the Mediterranean, the Caribbean, and Southeast Asia"--